Telomere length in early childhood and its association with attention: a study in 4–6 year old children - Croons, Hanne; Martens, Dries S.; Vanderstukken, Charlotte; Sleurs, Hanne; Rasking, Leen; Peusens, Martien; Renaers, Eleni; Plusquin, Michelle; Nawrot, Tim S. (Frontiers in Pediatrics, 2024)
Telomere length (TL), a marker of cellular aging, has been studied in adults with regard to its connection to cognitive function. However, little is known about the association between TL and cognitive development in children. This study investigated the interplay between TL and cognitive functioning in 283 Belgian children aged four to six years of the Environmental Influence on Aging in Early Life (ENVIRONAGE) birth cohort. Child leukocyte TL was measured using qPCR, while cognitive functioning, including attention and memory, was assessed using the Cambridge Neuropsychological Test Automated Battery (CANTAB). Linear regression models were employed to examine the association between TL and cognitive outcomes, adjusting for potential confounders. We found an inverse association between TL and the spatial errors made during the Motor Screening task (p=0.017), indicating a higher motor accuracy in children with longer telomeres. No significant associations were found between TL and other cognitive outcomes. Our results suggest a specific link between TL and motor accuracy but not with the other cognitive domains.